A Case Report of Multiple Gastrointestinal Stromal Tumors: Imaging Findings, Surgical Approach, and Review of the Literature - Tarallo, Mariarita; Carruezzo, Cristina; Dentice Di Accadia, Filippo Maria; Del Gaudio, Antonella; Caruso, Damiano; Polici, Michela; Crocetti, Daniele; Costi, Umberto; Polistena, Andrea; Panzuto, Francesco; Laghi, Andrea; Cavallaro, Giuseppe; et al. (Frontiers in Surgery, 2022)
Introduction Multiple gastrointestinal stromal tumors (GISTs) are rare tumors. Differential diagnosis between metastatic and multiple GISTs represents a challenge for a proper workup, prediction prognosis, and therapeutic strategy. Case presentation We present the case of 67-year-old man with computed tomography (CT) evidence of multiple exophytic lesions in the abdomen, reaching diameters ranging from 1 to 9 cm, without any signs of organs infiltration, and resulting positive at 18F-FDG-PET/CT. Laparoscopic biopsy revealed multiple GISTs, and surgical resection by using an open approach was performed to achieve radicality. Moreover, an extensive review of the current literature was performed. Results Small GISTs (<5 cm) can be treated by the laparoscopic approach, while in the case of large GISTs (>5 cm), tumor location and size should be taken into account to reach the stage of radical surgery avoiding tumor rupture. For metastatic GISTs, Imatinib represents the first choice of treatment, and surgery should be considered only in a few selected cases when all lesions are resectable. Conclusion Sporadic multiple GISTs are a rare event, imaging findings are not specific for GISTs, and biopsy requires a secure diagnosis and proper management. In the case of large lesions, with a high risk of vessels injury, laparotomy excision should be considered to achieve radicality and to avoid tumor rupture.